Estudo propositivo para identificação de indícios da Síndrome de Burnout em uma equipe da central de compras de uma holding na Serra Gaúcha - Lima, Carolina Oliveira de (My University, 2022)
The main objective of this study is to identify whether there are signs of Burnout Syndrome in a central purchasing department of a holding company in Serra Gaucha, by applying the Maslach Burnout Inventory - General Survey (MBI-GS) form in 63 professionals from the central purchasing department of a holding company in Serra Gaucha. The research is of a quantitative nature, descriptive level. The analysis of the results was based on the criteria established by Maslach, Jackson and Leiter (1996) and McLaurine (2008). The sample showed moderate levels in the three dimensions that make up the analysis, the Exhaustion dimension, which reflects emotional exhaustion due to work overload, the Cynicism dimension, which reflects an impersonal attitude toward work, indifference or disinterest in performing professional activities, and finally, the Work Effectiveness dimension, which reflects personal fulfillment at work and the expectations that the individual has. As far as Burnout is concerned, the sample presented a high level of the syndrome, reflecting a mean of 3.01, on a scale where the high level is considered from a mean of 2.43. Finally, future studies that analyze the influence of the organizational environment and how companies can offer a healthy environment in order to avoid Burnout Syndrome and behaviors arising from this syndrome are suggested. [resumo fornecido pelo autor]
O presente estudo apresenta como principal objetivo identificar se existem indícios da Síndrome de Burnout em uma central de compras de uma holding na Serra Gaúcha, através da aplicação do formulário Maslach Burnout Inventory - General Survey (MBI-GS) em 63 profissionais da central de compras de uma holding na Serra Gaúcha. A pesquisa é de natureza quantitativa, nível descritivo. A análise dos resultados foi baseada conforme os critérios estabelecidos por Maslach, Jackson e Leiter (1996) e McLaurine (2008). A amostra apresentou níveis moderados nas três dimensões que compõe a analise, dimensão de Exaustão, que reflete o esgotamento emocional devido à sobrecarga de trabalho, a dimensão de Cinismo que reflete a atitude impessoal em relação ao trabalho, indiferença ou desinteresse à realização das atividades profissionais e por último, a dimensão de Eficácia no Trabalho que reflete a realização pessoal no trabalho, as expectativas que o indivíduo possui. No que se refere ao Burnout, a amostra apresentou um nível alto da Síndrome, refletindo uma média de 3,01, em uma escala onde o nível alto é considerado a partir de uma média de 2,43. Por fim, sugere-se futuros estudos que analisem a influência do ambiente organizacional e como as empresas pode oferecer um ambienta saudável afim de evitar a Síndrome Burnout e além de comportamentos oriundos dessa síndrome. [resumo fornecido pelo autor]
Keywords: Administração; Burnout (Psicologia); Comunicação nas organizações; Trabalhadores - Serra, Região (RS) - Stress ocupacional